(untitled) (Quinto Sol, 2020)
During the 1930s in Argentina, the Catholic Church undertook the task of reconquering a society that, it considered, was far from doctrine. The Argentine Catholic Action was the lay branch-controlled by the ecclesiastical hierarchy-of this process of re-Christianization. Cultural issues concerned him because it was in this field, where the process of modernization seemed to move increasingly away from Catholic values. This article analyzes the view of the Argentine Catholic Action about the moral and cultural changes that crossed the Argentine society during the 1930s, based on the study of the following institutional publications: Boletín Oficial de la Acción Católica, Concordia, Anhelos, Boletín del Dirigente, Boletín de la Dirigente y Sursum. In particular, the institution’s statements about radio, film, press, fashion and the use of free time, products of mass culture that generated a special concern in the Catholic ranks, are examined.